2018
DOI: 10.5424/sjar/2017154-10779
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Trifolium resupinatum L. exposed to different extracts from leaves, flowers and shoots of Prangos ferulacea

Abstract: Prangos ferulacea is a member of Apiaceae family, is a popular fodder for livestock production and an important species in rangeland restoration. The objectives of the research are the comparative phytotoxic activity of aqueous and hydroalcoholic extracts obtained from different organs (flower, shoot and leaf) of P. ferulacea on antioxidant response of Trifolium resupinatum was investigated in a laboratory bioassay. Antioxidant enzyme activities including catalase (CAT), peroxidase (POD), ascorbic peroxidase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…In our study, the increase in MDA content indicated a high ROS concentration, which may have exceeded the scavenging threshold of antioxidant enzymes in T. roseoalba and T. chrysotricha , when compared to other Ipê species. These findings are in agreement with previous studies that reported inhibition in the activity of antioxidant enzymes under allelopathic stress (Sunmonu & Van Staden ; Bazdar & Sadeghi ; Coelho et al . ).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the increase in MDA content indicated a high ROS concentration, which may have exceeded the scavenging threshold of antioxidant enzymes in T. roseoalba and T. chrysotricha , when compared to other Ipê species. These findings are in agreement with previous studies that reported inhibition in the activity of antioxidant enzymes under allelopathic stress (Sunmonu & Van Staden ; Bazdar & Sadeghi ; Coelho et al . ).…”
Section: Discussionsupporting
confidence: 94%